2021
DOI: 10.1021/acsomega.1c03081
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Naphthoquinone Is a Potent Inhibitor of IRAK1 Kinases and the Production of Inflammatory Cytokines in THP-1 Differentiated Macrophages

Abstract: Quinones are a class of cyclic organic compounds that are widely distributed in nature and have been shown to exhibit anti-inflammatory, antioxidant, and anticancerous activities. However, the molecular mechanisms/signaling by which these molecules exert their effect are still not fully understood. In this study, a group of quinone-derived compounds were examined for their potential inhibitory effect against human IRAK1 and IRAK4 kinases in vitro. We have identified five compounds: 1,4-naphthoquinone, emodin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…In particular, the results showed that both 2-aryl-1,4-NQs and 4-aryl-1,2-NQs are expected to be biologically active as kinase inhibitors (see Table S5 ). In fact, the 1,4-NQ skeleton and other quinone-derived compounds had already been reported as active against kinases, by biochemical binding and molecular interaction with the kinases catalytic sites [ 39 ]. Kinase inhibitors are a large group of antineoplastic agents targeting protein kinases, which are altered in cancer cells leading to abnormal growth; hence, kinase inhibitors are considered a promising approach for anticancer drug development [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the results showed that both 2-aryl-1,4-NQs and 4-aryl-1,2-NQs are expected to be biologically active as kinase inhibitors (see Table S5 ). In fact, the 1,4-NQ skeleton and other quinone-derived compounds had already been reported as active against kinases, by biochemical binding and molecular interaction with the kinases catalytic sites [ 39 ]. Kinase inhibitors are a large group of antineoplastic agents targeting protein kinases, which are altered in cancer cells leading to abnormal growth; hence, kinase inhibitors are considered a promising approach for anticancer drug development [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lncRNA AK085865 binds to IL enhancer-binding factor 2 (ILF2), thereby regulating the ILF2/ILF3 complex and subsequently, miR-192/IL-1 receptor-associated kinase 1 (IRAK1) function ( 78 , 79 ). IRAK1 is the main mediator of toll-like receptor 4 (TLR4) activation and binds to TRAF6, ultimately leading to the induction of NF-κB, which is essential for lipopolysaccharide-mediated inflammatory response in macrophages ( 80 - 82 ). Xue et al found that silencing of the lncRNA MEG3 inhibited M1 polarization and promoted M2 polarization in macrophages, alleviating myocarditis.…”
Section: Resultsmentioning
confidence: 99%
“…However, it can be surmised by the ability of 1,4-naphthoquinone to modulate the IRAK1-mediated signaling pathway. Indeed, it has been recently shown that 1,4-naphthoquinone effectively inhibits IRAK1 enzymes in vitro and potently suppresses the production and secretion of key proinflammatory cytokine proteins in THP-1 cells . Several downstream signaling cascades such as NF-κB, JNK, and MAPKs can be activated by the IRAK1-mediated pathway. , Therefore, it would be interesting to define whether these pathways are involved in the 1,4-naphthoquinone-mediated FcRn induction mechanism in the future.…”
Section: Discussionmentioning
confidence: 99%
“…1,4-Naphthoquinone is a quinone-derived compound that has been shown to exhibit anti-inflammatory activity both in vitro and in vivo . , We have recently reported the ability of 1,4-naphthoquinone to target the IRAK1 enzyme, a master regulator of the IL1R/TLR immune signaling pathway in cells . Notably, IL1R/TLR regulates key downstream signaling proteins including NF-κB .…”
Section: Introductionmentioning
confidence: 99%